(untitled) (Scientific journal of the Fergana State University, 2025)
The article proves that the concept of "youth" and its division into groups is related not only to biological parameters but also to social characteristics such as the structure of society and culture (including language, the worldview in language). The complexity of the concept of "youth" is clarified through linguistic evidence, and many terminological combinations such as biological age, chronological age, somatic age, spiritual age, which are used in various scientific fields, have emerged. This is supported by examples from scientific research, which show that human life consists of several age stages. However, the number of these stages and the exact boundaries of age periods are discussed in the context of the studies. "Age stages" form an uncertain set of factors, such as cultural-historical, social, semiotic, age-related, and other factors. All these factors influence the understanding of the "youth" structure of society, the characteristics of different age groups, and the attitudes towards them. Additionally, there are stereotypical perceptions of youth in different linguocultural groups, which are expressed in various national languages. The study investigates how these stereotypical images can be explored based on different types of sources, such as lexicographical, text-based, discursive, and experiential data.